1989
DOI: 10.1136/oem.46.8.516
|View full text |Cite
|
Sign up to set email alerts
|

Malignant lymphomas and occupational exposures.

Abstract: The effects of potential risk factors for Hodgkin's disease (HD) and for non-Hodgkin lymphomas (NHL) were evaluated in a case-referent study encompassing 54 cases ofHD, 106 cases of NHL, and 275 referents, all alive. Exposure information was obtained by questionnaires posted to the subjects. Crude rate ratios were increased for various occupational exposures including solvents, welding, wood preservatives, phenoxy acids, and fresh wood (sawmill workers, lumberjacks, paper pulp workers). After further analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 19 publications
5
65
0
1
Order By: Relevance
“…We found a significant association between exposure to phenoxyacetic acids and chlorophenols and malignant lymphoma, both NHL and Hodgkin disease (Hardell et al 1981). The results for NHL were also published separately (Hardell et al 1994) and have been replicated by other research groups both in Sweden (Persson et al 1989) and in other countries ; for updated review, see Hardell et al 2003).…”
Section: Phenoxyacetic Acids and Chlorophenolssupporting
confidence: 66%
See 2 more Smart Citations
“…We found a significant association between exposure to phenoxyacetic acids and chlorophenols and malignant lymphoma, both NHL and Hodgkin disease (Hardell et al 1981). The results for NHL were also published separately (Hardell et al 1994) and have been replicated by other research groups both in Sweden (Persson et al 1989) and in other countries ; for updated review, see Hardell et al 2003).…”
Section: Phenoxyacetic Acids and Chlorophenolssupporting
confidence: 66%
“…One explanation might be that newer organic solvents are chemically different from earlier ones and are handled under better hygienic conditions than before (Axelson and Hogstedt 1994). In another Swedish study with exposures during the same period (Persson et al 1989), the attributable fraction was calculated to be 16%.…”
Section: Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was in contrast to our previous results on NHL, 18 but another Swedish study also found an association between creosote and NHL. 41 Chlorophenols have been the most common group of impregnating agents in Sweden, but were banned in 1977. In our first NHL study, reflecting exposures mainly during the time these substances were used, we found a strong association with NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from studies of TCE-exposed aerospace and aircraft workers are not supportive of an increased risk of NHL. [205][206][207][208] Other occupational cohorts in the US, 209 Sweden, 210 Finland 211 and Denmark, 212,213 and 2 case-control studies 117,214 have reported positive associations, albeit without evidence of exposure-response relationships based on urinary trichloroacetic acid (TCA) concentrations. 210,211 Significant positive associations with several NHL types were reported among men and women from New Jersey communities where TCE had been found in drinking water.…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%